Blended Learning Model During the Covid-19 Pandemic: Analysis of Student’s' Mathematical Disposition - Fadillah, Ahmad; Nopitasari, Dian; Pradja, Barra P (JTAM (Jurnal Teori dan Aplikasi Matematika), 2020)
The purpose of this study is to describe the mathematical disposition of students who use blended learning during the Covid-19 pandemic. This research is a descriptive qualitative research. The research subjects were four students from the sixth semester of mathematics education study program. The research instrument was a student mathematical disposition questionnaire. The results of the study concluded that the average level of mathematical disposition of students was classified as moderate. If seen from the indicators, only the monitor and evaluate indicators are classified as high category. Indicators of persistence and perseverance, especially when lecturers present interesting contextual problems. Many indicators of curiosity arise when lecturers invite students to be active in learning, for example students are invited to study in groups. Many self-confidence indicators appear when lecturers ask students questions. While many flexible indicators appear when lecturers give open ended questions.